The Colombian Caribbean Sea: a tropical habitat for the Vulnerable sperm whale Physeter macrocephalus?. Issue 6 (20th November 2022) - Avila, Isabel Cristina; Farías-Curtidor, Nohelia; Castellanos-Mora, Luisa; do Amaral, Karina Bohrer; Barragán-Barrera, Dalia C.; Orozco, Carlos Andrés; León, Jorge; Puentes, Vladimir
Abstract: We studied the sperm whale Physeter macrocephalus in the Colombian Caribbean by combining data from our offshore surveys of behaviour, encounter rate, group structure and density with data from the literature. We describe for the first time the potential distribution of sperm whales in the Colombian Caribbean, using sighting and acoustic data obtained during our surveys, published information, and opportunistic encounters during 1988–2020. We conducted surveys on seismic vessels over 703 days during 2011–2016, covering an area of 68, 904 km 2 . We recorded 98 individuals in a total of 50 groups, a density of 1.42 individuals per 1, 000 km 2 . To determine the potential distribution of the species, we built Maxent models with uncorrelated environmental variables at five depths (from the surface to c. 2, 000 m). The model for 1, 000 m depth had the best performance, with areas of high probability of occurrence of sperm whales in the south and north-east Colombian Caribbean over the shelf break to waters up to c. 3, 000 m deep, at a median distance of 107 km from the coast, and near the Archipelago of San Andrés, Old Providence and Saint Catherine in the north-west. This area may be an important tropical habitat for sperm whales, in which they socialize, rest, breed and feed. Our study underlines the importance of monitoring marine mammals offshore and describes the potential distribution of sperm whales in the Colombian Caribbean, supporting conservation actions for this Vulnerable species, which is currently facing several threats in this region.